Assessing instream habitat suitability and hydraulic signatures of geomorphic units in a reconstructed single thread meandering channel. Issue 6 (15th December 2015) - Cockburn, J.M.H.; Villard, P.V.; Hutton, C.
Abstract: Stream channel reaches consist of a series of geomorphic units (e.g. pools, runs and riffles) that mitigate flow velocity and provide a variety of aquatic habitat. The hydraulic signature of each geomorphic unit is unique and should remain so during variable flow conditions in order to satisfy habitat requirements. We use the hydraulic signatures measured at different geomorphic units in a recent channel realignment project to evaluate suitability of reaches and geomorphological units for target fish species. In 2009, 650 m of creek and valley were realigned in Brampton, Ontario, to facilitate development. In 2013, water velocity, depth, temperature and channel substrate were measured at cross‐sections between 1 May and 15 October. The assessment illustrated that while geomorphic units have unique signatures during moderate to low‐flow conditions, at high‐flow conditions the boundaries between geomorphic units blurred. Furthermore, our findings suggest that suitable water depth, velocity and temperature conditions existed at least 68% of the time over the entire study period but was reduced during the estimated spawning period for the target species. Specifically, water depth was only ideal for approximately 38% of the spawning period. Finally, in cases where both geomorphic and ecologic systems interface (e.g. channel restoration), it is important to view the whole picture. This study contributes to the on‐going discussion on restoration and success and is particularly useful in light of recent stream restoration trends in rapidly expanding urban regions around the globe. Copyright © 2015 John Wiley & Sons, Ltd.